Ceftriaxone-Induced Pancytopenia: A Case Report - Edin Karisik; Zorica Stanojevic-Ristic; Marija Jevtic; Julijana Rasic; Miljana Maric; Milica Popovic (Hematology Reports, 2025)
Background: Cephalosporins are considered safe antibiotics. However, serious hematological abnormalities may occur, although rarely, after their therapeutic use. Case Presentation: We present a case of pancytopenia in a 72-year-old female patient treated with ceftriaxone for a urinary tract infection. After five days of therapy, pancytopenia was observed. Other causes were excluded through extensive diagnostic evaluation, including immunological tests, viral serologies, bone marrow aspiration, and peripheral blood smear. The patient’s clinical condition significantly improved following the discontinuation of ceftriaxone and the administration of granulocyte colony-stimulating factor (G-CSF). Bone marrow findings revealed hypocellularity without malignant infiltration, and peripheral smear showed no dysplasia, blasts, or hemolysis. Conclusions: This case demonstrates that ceftriaxone, although widely regarded as a safe antibiotic, can induce rare but serious hematologic complications such as pancytopenia. A high index of suspicion is required when patients on antibiotic therapy develop unexplained cytopenias. Detailed medication history, exclusion of other causes, and prompt discontinuation of the suspected drug are essential. The patient’s favorable outcome supports the likelihood of an idiosyncratic, immune-mediated mechanism. Future research should explore pharmacogenomic screening in patients at increased risk, particularly involving HLA variants.